THE THEORETICAL AND APPLIED ISSUES ON DOCUMENTARY HERITAGE AT THE INTERNATIONAL BIBLIOLOGICAL CONFERENCE - SĖDAITYTĖ, EDITA (Knygotyra, 2012)
Vilniaus universiteto Knygotyros ir dokumentotyros institutas Universiteto g. 3, LT-01513 Vilnius, Lietuva El. paštas: editasedaityte@gmail.com